Graves’ disease thyrotoxicosis and propylthiouracil related agranulocytosis successfully treated with therapeutic plasma exchange and g-csf followed by total thyroidectomy. - Anna Candoni (Mediterranean Journal of Hematology and Infectious Diseases)
Antithyroid drugs can be a rare cause of agranulocytosis (0.5% of treated patients). Suspension of these drugs is mandatory in these patients and may result in worsening hyperthyroidism. We report the case of a 27-year-old woman who is 3 months post-partum, breastfeeding, and suffering from Graves’ disease hyperthyroidism treated first with methimazole and then with propylthiouracil due to a methimazole allergy. She was admitted for urosepsis and agranulocytosis. The patient was diagnosed with propylthiouracil related agranulocytosis, diffuse toxic goiter, and thyro-gastric syndrome. Antithyroid drug therapy was stopped resulting in a worsening of thyrotoxicosis. Agranulocytosis was treated with 8 doses of G-CSF with full recovery. To rapidly restore euthyroidism and to perform a thyroidectomy, the patient received 6 plasmapheresis procedures, to clear thyroid hormones and anti-TSH receptor antibodies from the blood, resulting in a pre-surgical euthyroid state without antithyroid drugs. One year after thyroidectomy, the patient is well on thyroid hormone replacement therapy.